A Novel C22 Terpenoid from the Cultured Perovskia atriplicifolia. Issue 6 (24th May 2016) - Jiang, Zhi‐Yong; Zhu, Le‐Yu; Zhou, Jun; Hu, Qiu‐Fen; Yang, Guang‐Yu; Huang, Xiang‐Zhong; Liu, Wen‐Xing; Gao, Lu; Li, Gan‐Peng; Xia, Fu‐Ting
Abstract : A novel terpenoid, named perovskiaol (1 ), was isolated from the cultured Perovskia atriplicifolia . Its structure was elucidated by comprehensive spectroscopic analysis as well as by quantum chemical computation of electronic circular dichroism spectra. Perovskiaol (1 ) was a novel C22 terpenoid containing a unique D ‐ring simultaneously fused with rings A, B, and C, and encountered in nature for the first time. Cytotoxic bioassay suggested perovskiaol (1 ) possessed significant cytotoxic activity inhibiting NB4, A549, and HepG 2 cell lines with IC 50 values of 2.35, 1.47, and 0.81 μm, respectively. Abstract :